Almost a woman - Santiago, Esmeralda; Santiago, Esmeralda; Santiago, Esmeralda (New York : Vintage Books, 1999)
"Negi," as the author's family affectionately calls her, leaves rural Macun in 1961 to live in a three-bedroom tenement apartment with seven siblings, an inquisitive grandmother, & a strict mother who won't allow her to date. At thirteen, Negi yearns for her own bed, privacy, & her father, who remains in Puerto Rico. Translating for Mami at the welfare office in the morning, starring as Cleopatra at New York's Performing Arts High School in the afternoon, & dancing salsa all night, she also seeks to find balance between being American & Puerto Rican. When Negi defies her mother by going on a series of dates, she finds the independence brings challenges. At one a universally poignant coming-of-age tale & a heartfelt immigrant's story, this book is the author's journey into womanhood.
Continues: When I was Puerto Rican; continued by: The Turkish lover.
Keywords: Santiago, Esmeralda -- Childhood and youth; Puerto Rican women -- New York (State) -- New York -- Biography; Puerto Ricans -- New York (State) -- New York -- Biography; New York (N.Y.) -- Biography; Brooklyn (New York, N.Y.) -- Biography